53-3x=8x-20

Simple and best practice solution for 53-3x=8x-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53-3x=8x-20 equation:


Simplifying
53 + -3x = 8x + -20

Reorder the terms:
53 + -3x = -20 + 8x

Solving
53 + -3x = -20 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
53 + -3x + -8x = -20 + 8x + -8x

Combine like terms: -3x + -8x = -11x
53 + -11x = -20 + 8x + -8x

Combine like terms: 8x + -8x = 0
53 + -11x = -20 + 0
53 + -11x = -20

Add '-53' to each side of the equation.
53 + -53 + -11x = -20 + -53

Combine like terms: 53 + -53 = 0
0 + -11x = -20 + -53
-11x = -20 + -53

Combine like terms: -20 + -53 = -73
-11x = -73

Divide each side by '-11'.
x = 6.636363636

Simplifying
x = 6.636363636

See similar equations:

| (m-3)(m-3)=64 | | m^2-9-64=0 | | 3x-34=2x-5 | | 4/x+1=2x/x+6 | | 195-3x=33x+23 | | 33=6c-3 | | -86-7x=8x+149 | | rd=309d | | 30f=f^2 | | 4(-1x-3)=-52 | | 7(4x+1)=-91 | | 8-7x=x-48 | | -7x-1=-5x-11 | | 6-3x-3x=-12 | | 5x+3+x=-33 | | 5(-8+4x)=160 | | 3(-8+7x)=102 | | 10+4x=x-2 | | 6x-6=-3x-60 | | (-22)-[7+(-6)]= | | -7-5x+3x=13 | | 7x+8+6x=47 | | [(-22)-7]+(-6)= | | (x+a)(x+3)=x^2-2a-15 | | 1=125000+3000x | | 9x^3+6kx^2+(1-3k)x=0 | | (2k-7)(2k-3)=0 | | 7m+21=3+33 | | x^2-4x+k=0 | | 7x-5=10-3x | | 2x-17=-39 | | 5x-4=2-x |

Equations solver categories